Unveiling the Pharmacological Mechanisms of Eleutheroside E Against Postmenopausal Osteoporosis Through UPLC-Q/TOF-MS-Based Metabolomics - Ma, Yong-Sheng; Hou, Zhan-Jiang; Li, You; Zheng, Beng-Beng; Wang, Jia-Ming; Wang, Wen-Bo (Frontiers in Pharmacology, 2020)
Postmenopausal osteoporosis (PMOP) is a common metabolic bone disease in postmenopausal women in the Worldwide, and seriously affects the quality of life of middle-aged and elderly women. Therefore, there is an urgent need to discover a highly effective drug for PMOP treatment. In this study, ultra-high performance liquid tandem quadrupole time-of-flight mass spectrometry (UPLC-Q/TOF-MS) was used to analyze the urine metabolic profiling and potential biomarkers, the relevant metabolic network of PMOP rats, and further to evaluate the intervention effect of Eleutheroside E (EE) against PMOP. Using multivariate statistical analysis combined with UPLC-Q/TOF-MS, a total of 27 biomarkers were identified, which related with 16 metabolic pathways, mainly involving steroidogenesis, beta oxidation of very long chain fatty acids, glutathione metabolism, carnitine synthesis, estrone metabolism, oxidation of branched chain fatty acids, etc. After treatment of EE, these biomarkers were markedly regulated, mainly involving steroid hormone biosynthesis, arachidonic acid metabolism, primary bile acid biosynthesis, indicating that EE had the therapeutic effect on PMOP. This study identified the potential urine metabolic markers and related metabolic pathways of the PMOP, explained the metabolic effect and pharmacological mechanisms of EE against PMOP, and provided a basis for the pharmacological study of EE.